2018
DOI: 10.7809/b-e.00327
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bush encroachment management on plant response and animal distribution

Abstract: Abstract:The transformation of grassland by bush encroachment causes socioeconomic problems in arid and semi-arid regions. At the moment, de-bushing is the only way to control bush encroachment. In this context, we conducted two independent projects within SASSCAL. First, in a greenhouse experiment, we investigated the morphological plant response to damage of four diff erent bush encroacher species in order to understand if intervention in the plants' early life stage may reasonably fi ght bush encroachment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…More interesting was our fi nding of a severe response in the morphological characteristics of the plants (see bush encroachment chapter, Stolter et al, 2018). Our feeding trial clearly demonstrated that neither do the measured PSMs lead to a total avoidance nor does the high nitrogen content lead to a feeding preference in goats.…”
Section: Synthesis and Outlookmentioning
confidence: 75%
See 2 more Smart Citations
“…More interesting was our fi nding of a severe response in the morphological characteristics of the plants (see bush encroachment chapter, Stolter et al, 2018). Our feeding trial clearly demonstrated that neither do the measured PSMs lead to a total avoidance nor does the high nitrogen content lead to a feeding preference in goats.…”
Section: Synthesis and Outlookmentioning
confidence: 75%
“…Neither sheep nor goats showed diff erences in selection between previously damaged or undamaged plants (for more detailed information, see the bush encroachment chapter, Stolter et al, 2018). Unlike goats, the chosen sheep breed (Cameroon blackbelly) totally avoided all four plant species, whether the plants were damaged or not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vector and host responses to WPE will vary among species depending on resource needs and life histories. Grassland‐inhabiting species that gain no resources from WPE may decline, and generalists and other species that gain resources may increase (Coppedge et al., 2001; Stolter et al., 2018). The responses of all VBD system components will also vary relative to features of WPE systems (e.g.…”
Section: Conceptual Framework For Woody Plant Encroachment Effects On...mentioning
confidence: 99%
“…6), manual tree cutting, stem burning (Tainton 1999;Suttie et al 2005;Lukomska et al 2014;Reed et al 2015;Harmse et al 2016;Hare et al 2020). There are also more long-term approaches of introducing (more) browsers and adapting the veld and livestock management in a way that will slow down bush encroachment or potentially even put it to a halt (Tainton 1999;Biggs et al 2009;Kellner 2009;Kgosikoma and Mogotsi 2013;Stolter et al 2018;Swemmer and Ward 2019).…”
Section: Savanna Dynamics and Land Degradationmentioning
confidence: 99%